Slag-containing composite materials for road construction - Korohodska, A.; Shabanova, H. M.; Shumeiko, V.; Shchukina, Lyudmyla; Borysenko, Oksana; Kryvobok, R. V.; Sakhnenko, M. D.; Lisachuk, G. V. (Publishing House "Helvetica", 2024)
The scientific material provides an analysis of the situation in Ukraine with the most common waste of the metallurgical industry - slag and suggests ways to solve this problem. The publication presents the results of research on obtaining rational compositions of alkaline slag binders using blast furnace dump and granulated slag. It is noted that the involvement of various groups of industrial waste in the production of paving slabs will expand the raw material base of domestic enterprises, reduce the cost of production by 2-4 times without compromising its quality and reduce the consumption of primary raw materials by up to 80%. Following these developments, waste generators and landfill operators will be able to reduce the amount of waste accumulated and the costs associated with environmental protection measures, which will minimise the negative impact of accumulated waste on the environment and human health. Designed for researchers, postgraduates and students specialising in refractory non-metallic and silicate materials. All rights reserved. The monograph was published with the grant support of the National Research Foundation of Ukraine within the framework of the project 2021.01/0316 "Development of composite materials for road construction based on multi-tonne waste".
Keywords: monograph; slag-containing composite materials; road construction; waste management reform; the problem of waste; environmental protection